Multifunctionalization of cotton fabrics with polyvinylsilsesquioxane/ZnO composite coatings. (1st November 2018) - Mai, Zhonghua; Xiong, Zhewen; Shu, Xin; Liu, Xin; Zhang, Hongwei; Yin, Xianze; Zhou, Yingshan; Liu, Min; Zhang, Ming; Xu, Weilin; Chen, Dongzhi
Graphical abstract: Highlights: A composite coating was developed by combing with PVSQ and ZnO nanoparticles. Functionalized cotton fabrics were obtained by treatment of the composite coatings. The treated cotton fabrics exhibit excellent UV shielding and superhydrophobicity. The composite coatings can endow cotton fabric with good mechanical properties. Abstract: Ultraviolet (UV) shielding, superhydrophobic and antimicrobial cotton fabrics were fabricated using functional coatings combined with advantages of polyvinylsilsesquioxane and ZnO nanoparticles by solution immersion. The influence of composite coatings on surface morphology, water-repellence, UV shielding property, mechanical property, thermal degradation behavior and antibacterial property of the cotton fabrics was investigated respectively. It is evidently found that the cotton fabrics functionalized by composite coatings exhibited excellent UV shielding, durable superhydrophobic and antimicrobial properties as compared to the reference materials. Most notably, the mechanical properties of cotton fabrics was significantly improved by surface treatment of the composite coatings without compromising their thermal stability as compared to the pristine cotton fabric. This strategy for fabricating UV shielding and superhydrophobic cotton fabrics will guide for developing advanced functional textile in the future work, which will likely be found in many applications such as advanced protective textiles, oil/water separation, water-proof, antibacterial and self-cleaning fields.